Implementation of the Cita Sembada Program by Pertagas OEJA using the PDCA cycle approach as a strategy for community empowerment and sustainable development in Ganggang Panjang Village - Miracahyani, Adhelia Hasri; Almaida, Zwita; Satrya, Al Rosyid Anggi; Utomo, Anang Wahyu (Prospect Publishing, 2025)
Cita Sembada program is inititated by Pertamina Gas Operation East Java Aera (OEJA) as an initiave for Corporate Social Responsibility (CSR) based on company's core value which is focused on managing water resource, environment, and economy continually. This research utilizes qualitative descriptive method using data collection by doing interviews, observations, and documentation. The analysis is done using Plan-Do-Check-Act (PDCA) to evaluate the program's effectivity and sustainability. Result shows that Tirta Sembada sub-program improves the agricurtural productivity by creating a new irrigation system and utilizing Ecobrick as the supporting pipe (ECOPORI). Moreover, Bhumi Sembada sub-program successfully reduce waste volume by sorting and bipore system, while Dhana Sembada strengthen the local economy by the development of Punden Reco tourism. Overall, the program improves the harvesting period into three times a year, while reducing plastic waste from households, and increases the public awareness and participation in environmental management.